2014
DOI: 10.4236/ojgen.2014.45031
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization on the Early Developmental Stages of the Egyptian Toad <i>Bufo regularis</i> Reuss

Abstract: The present study aimed to investigate changes in the protein contents using SDS-PAGE, also using the random amplified polymorphic DNA (RAPD-PCR) assay to identify changes in DNA concentration in the embryos of Egyptian toad Bufo regularis. Our experiment started when tadpoles began to feed. The adapted embryos were divided into 3 large tanks of 200 embryos each, collections of samples started from feeding age every three days. Cluster method was used to indicate the distinct distance between the band patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…The investigators suggested that the increment in the density of staining may be due to a production of new proteins which increased as the development of the tadpoles progressed. This suggestion is in agreements with the analysis of proteins by electrophoresis (SDS-PAGE) and DNA electrophoresis analysis (RAPD-PCR) where new bands appeared and the thickness of the bands increased, respectively, as the development of the tadpole progressed (Sayed et al 2014).…”
Section: Discussionsupporting
confidence: 85%
“…The investigators suggested that the increment in the density of staining may be due to a production of new proteins which increased as the development of the tadpoles progressed. This suggestion is in agreements with the analysis of proteins by electrophoresis (SDS-PAGE) and DNA electrophoresis analysis (RAPD-PCR) where new bands appeared and the thickness of the bands increased, respectively, as the development of the tadpole progressed (Sayed et al 2014).…”
Section: Discussionsupporting
confidence: 85%
“…The adapted embryos were described according to [16] and selected according to [17] subdivided into 3 large tanks (200 embryos per each). The conditions of the experiment were the same as that of acclimatization with daily changing all the tap water.…”
Section: Experimental Designmentioning
confidence: 99%